Contemporary Homeschooling Arrangements: An Analysis of Three Waves of Nationally Representative Data. Issue 5 (July 2023) - Cheng, Albert; Hamlin, Daniel
Dramatic growth in the homeschool population in recent decades has coincided with an increase in the methods used to educate homeschooled children. However, researchers tend to treat homeschooled children as a uniform group without accounting for vastly different homeschooling arrangements. In this study, we examine the prevalence of four types of homeschool arrangements by pooling three cross-sectional waves of nationally representative data on American homeschool families ( n = 1, 468). Results indicate that most homeschool families supplement home education with cooperative instructors and private tutors, online education, and brick-and-mortar schooling. Families who do not use these resources are declining. They are also more likely to be White, less educated, and residing in the South region. Homeschool families whose children attend brick-and-mortar schools part-time are less likely to be White and more likely to reside in urban areas. Future research is needed to explore outcomes across different homeschool arrangements.